Denial attitude and behavior as a response to the COVID-19 pandemic: A qualitative study - Sabiqotul Husna (Universitas Ahmad Dahlan, 2021)
Amid various reactions and public responses to the uncertain situation and changes during the COVID-19 pandemic, some groups and individuals worldwide expressed denial attitudes and behavior, including in Indonesia. This paper aimed to explore denial attitude and behavior, particularly on social learning and observational learning theory. A qualitative survey method with open-ended questions was applied to gather data from 15 individuals who believed the COVID-19 pandemic was part of conspiracy theory and or does not exist. The results show a social learning process leads to the occurrence of attitudes and behaviors that deny the current existence of the COVID-19. Observational learning with a reference group strengthens individuals adapting and forming behavior similar to their reference group. Believing conspiracy theory and having negative perception and behavior towards medical workers are types and characteristics of attitude and behaviors in denying the COVID-19 pandemic. The denial attitude and behavior can ultimately be concluded as a psychosocial response that emerged due to social learning and individual factors, including insufficient access to reliable information and conspiracy theories that were received massively from social media and broadcast message groups. These findings suggest that more attention needs to be given to social and individual factors as causes of the COVID-19 pandemic denial.